Implications of Correspondence Inference Attribution Theory & Behavioral Jurisprudence Theory: Judge's Conciderations on Conscience - Sinaga, Cindy Debora; Somawijaya, Somawijaya; Takariawan, Agus (Faculty of Law, Universitas Pattimura, 2022)
Introduction: This article analyzes the implications of the attribution correspondence inference theory and whether the urge of conscience as affect in the Defendant is the reason for the abolition of the sentence? also behavioral jurisprudence theory on judges' considerations, where it's often a discourse in Indonesia. It is necessary to explore the human values contained in Defendant.Purposes of the Research: The objectives of the research are: First, to provide an analysis of how the theory of attribution correspondence inference to the judge's considerations in determining the circumstances that form the basis of sentencing and knowing whether the urge of conscience as affect in the Defendant is the reason for the abolition of the crime? Second, providing an analysis related to the urgency of behavioral jurisprudence theory in creating fair decisions based on the conscience of the judge.Methods of the Research: The normative legal research method uses a statutory approach, a conceptual approach, and comparisons with different legal system which are based on library research in collecting research legal materials.Results of the Research: The results are: First, the attribution correspondence inference theory can be used as consideration for judges’ considerations in determining to mitigate and aggravating circumstances in Indonesia and with a study of criminal law and the theory that the urge of conscience as affect the defendant can be used as a consideration of mitigating circumstances for the defendant, as well as conditional punishment. Second, the behavioral jurisprudence theory approach has urgency in understanding the behavior of a person doing an act or the judge in making a fair decision.